Treatment modalities and clinical outcomes in patients with gestational trophoblastic disease - Laila, Nousheen; Azim, Nazma; Nasim, Rehnuma; Islam, Farzana; Khan, Sadia Sultana (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Gestational trophoblastic disease (GTD) encompasses a diverse group of disorders characterized by abnormal trophoblastic tissue proliferation, including premalignant conditions like hydatidiform moles and malignant types such as choriocarcinoma and persistent trophoblastic disease, which carry significant malignant potential. The purpose of this study was to evaluate the effectiveness of various treatment modalities and the clinical outcomes in patients diagnosed with gestational trophoblastic disease. The aim of the study was to evaluate the effectiveness of various treatment modalities and the clinical outcomes in patients diagnosed with gestational trophoblastic disease. Methods: This descriptive cross-sectional study, conducted at the Department of Obstetrics and Gynaecology, Sir Salimullah Medical College and Mitford Hospital, Dhaka (November 2012 - November 2013), included 50 cases of gestational trophoblastic disease (GTD). Inclusion criteria were fresh, incompletely treated, and recurrent GTD cases. Data were collected via a pretested questionnaire, analyzed using SPSS, and presented as descriptive statistics. Ethical approval and informed consent were obtained from all participants. Results: Among 50 GTD cases, 60% were complete moles, with 94.44% of persistent disease linked to prior molar pregnancies. P/V bleeding was the most common symptom. Choriocarcinoma showed 50% metastasis, mainly to lungs, and 86% remission with EMACO therapy. Suction evacuation treated 56% of molar pregnancies, with 13.5% progressing to persistent mole and 4.5% to choriocarcinoma. Conclusions: This study highlights the importance of early detection, timely treatment, and regular follow-up in improving outcomes for patients with gestational trophoblastic disease.